Clinical frailty scale is useful in predicting return-to-home in patients admitted due to coronavirus disease - Koki Kawamura; Aiko Osawa; Masanori Tanimoto; Hitoshi Kagaya; Toshihiro Matsuura; Hidenori Arai (BMC Geriatrics, 2023)
Abstract Background The spread of the novel severe acute respiratory syndrome coronavirus 2 infection has been prolonged, with the highly contagious Omicron variant becoming the predominant variant by 2022. Many patients admitted to dedicated coronavirus disease 2019 (COVID-19) wards (COVID-19 treatment units) develop disuse syndrome while being treated in the hospital, and their ability to perform activities of daily living declines, making it difficult for hospitals to discharge them. This study aimed to investigate the relationship between the degree of frailty and home discharge of patients admitted to a COVID-19 treatment units. Methods This study retrospectively examined the in-patient medical records of 138 patients (82.7 ± 7.6 years old) admitted to a COVID-19 treatment unit from January to December 2022. The end-point was to determine the patients’ ability to be discharged from the unit directly to home; such patients were classified into the ‘Home discharge’ group and compared with those in the ‘Difficulty in discharge’ group. The degree of frailty was determined based on the Clinical Frailty Scale (CFS), and the relationship with the endpoint was analysed. A receiver operating characteristic (ROC) curve was created and the cut-off value was calculated with the possibility of home discharge as the state variable and CFS as the test variable. Logistic regression analysis was conducted with the possibility of home discharge as the dependent variable and CFS as the independent variable. Results There were 75 patients in the Home discharge group and 63 in the Difficulty in discharge group. ROC analysis showed a CFS cut-off value of 6 or more, with a sensitivity of 70.7% and a specificity of 84.1%. The results of the logistic regression analysis showed a significant correlation between possibility of home discharge and CFS even after adjusting for covariates, with an odds ratio of 13.44. Conclusions Based on the evaluation of the degree of frailty conducted in the COVID-19 treatment unit, it was possible to accurately predict whether a patient could be discharged directly to home after treatment CFS could be an effective screening tool to easily detect patients requiring ongoing hospitalisation even after the acute phase of treatment.